Pendidikan Kewarganegaraan Berbasis Adat: Studi Kasus Masyarakat Kampung Naga - Denda Ginanjar; Mohamad Sutisna; Ari Muhamad Rahman; Hani Nuraeni; Bayu Bagus Mulyana; Mas Fierna Janvierna Lusie Putri (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2024)
In the era of globalization, indigenous communities are increasingly at risk of losing their identity and traditional values. Kampung Naga, one of the oldest traditional villages in Indonesia, has a complex social and cultural system. This study aims to deeply examine the role of traditional institutions in shaping and instilling civic values in the indigenous community of Kampung Naga. Through a qualitative case study method, this research analyzes the structure of traditional institutions, decision-making mechanisms, and customary practices related to citizenship. The results of the study show that traditional institutions have a central role in preserving the values of mutual cooperation, consensus-based decision-making, and respect for nature. Customary practices such as traditional ceremonies, village meetings, and social sanctions serve as effective social control mechanisms in shaping the character of good citizens. This study concludes that the traditional institutions of Kampung Naga can serve as a model for the development of character education and citizenship rooted in local values.